KHAI THÁC TẬP MỤC LỢI ÍCH CAO CÓ LỢI NHUẬN ÂM TRONG CƠ SỞ DỮ LIỆU PHÂN TÁN DỌC - Cao, Tùng Anh (Trường Đại học Đà Lạt, 2023)
High Utility Itemset (HUI) mining is an important problem in the data mining literature that considers the utilities for businesses of items (such as profits and margins) that are discovered from transactional databases. There are many algorithms for mining high utility itemsets (HUIs) by pruning candidates based on estimated and transaction-weighted utilization values. These algorithms aim to reduce the search space. In this paper, we propose a method for mining HUIs with negative unit profits from vertically distributed databases. This method does not integrate databases from the relevant local databases to form a centralized database. Experiments show that the run-time of this method is more efficient than that of the centralized database.